Analisis Implementasi Core Value Berakhlak terhadap Kinerja Pegawai Aparatur Sipil Negara di Kantor Pusat Badan Kepegawaian Negara - Silvia Agustina; Winna Sarikusumaningtyas (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
The launch of Core Value BerAKHLAK and ASN Employer Branding "Proud to Serve the Nation" aims to encourage civil servants across all government sectors to adopt these values as guidelines in their thinking and working. The implementation of the Core Value BerAKHLAK at the National Civil Service Agency is carried out through several stages, from socialization, internalization, to evaluation of effectiveness. aims to encourage civil servants across all government sectors to adopt these values as guidelines in their thinking and working. The implementation of the Core Value BerAKHLAK at the National Civil Service Agency is carried out through several stages, from socialization, internalization, to evaluation of effectiveness. A behavioral guide for civil servants is developed to ensure these values are applied in every aspect of their work. Impact analysis shows that the implementation of the Core Value BerAKHLAK has successfully improved the performance and professionalism of civil servants, evidenced by the awards received and the increase in performance and stakeholder satisfaction indexes.